COVID-19 vaccine acceptance and its determinants among Vietnamese teachers: a web-based cross-sectional survey - Anh Thi-Kim Le; Thanh Quoc Pham; Long Thanh Nguyen; Tien Dung Pham; Nhu Van Ha (AIMS Press, 2022)
Objectives: This paper aimed to describe acceptance of the COVID-19 vaccine and its determinants among Vietnamese teachers. Methods: This was a web-based cross-sectional survey with a sample of 17,176 teachers from kindergarten to high school who currently reside in Vietnam. A participant who exhibited "acceptance" towards the vaccine gave the following response: "have the readiness to get COVID-19 vaccine". Results: About 88% of all participants were accepting of the COVID-19 vaccine, while 70.4% were willing to pay (WTP) for it. The vaccine acceptance rate increased by age with odds ratios (OR) of 1.65 (1.41-1.93), 1.96 (1.67-2.29), and 2.4 (1.95-2.95) for the age groups 30-39, 40-49, and 50-59 respectively, when compared to the 18-29 age group. Male were found to be more likely to accept the vaccination than females (OR = 1.16; 95% CI: 1.02-1.31); teachers without a chronic disease were 4.13 times (95% CI: 2.67-6.37) more likely to accept the vaccine than those with an underlying condition. Willingness to pay and beliefs about the safety and efficacy of the vaccine were major factors in driving participants' responses. Conclusion: A high proportion of COVID-19 vaccine acceptance is a promising indicator of high coverage among this priority group for vaccination. Communication campaigns should consider addressing determinants uncovered by this study to achieve better vaccine acceptance.